Analysis of Iran’s Energy Strategies in Horizon 2040: Within the framework of global energy scenarios - Abdolrasoul Ghasemi; Atefeh Taklif; Teymour Mohammadi; fereshteh mohammadian (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2017)
The main purpose of this study is to evaluate general strategies of the national document of Iran's energy strategy according to World Energy Council scenarios and based on robust strategy framework, to doing so, a standard political framework and its requirements was introduced and then surveyed to realize which strategies are robust to apply the mentioned political framework in the world depicted by each scenario. In compare to standard political framework in National Energy Strategy Document, no suggestion on energy sources diversification and new energies is proposed and no strategy is seen in the field of energy industry safety and to reduce the political and economic risks of investors. Eventually based on robust strategy, we only have two robust strategy in research and development context. But, in other seven political domain no robust strategy is observed, especially in Hard Rock Scenario, no strategy was seen in five axis from eight axis of main political context. Thus, it is advised to review the existing strategies according to opportunities and threats available in any scenario, and to formulate a comprehensive pattern for national energy policy accordingly. In this regards, it seems very important to design a mechanism to develop new energies, to reduce the political and economic risks for oil companies, to create a surveillance and evaluation system for national energy data, to provide a legal mechanism for negotiation, and finally to select an administrator capable to aggregate resources to implement the strategies in the best way possible